Análise fitoquímica de duas espécies de Rutaceae: Helietta apiculata Benth e Zanthoxylum fagara (L.) Sarg. - Fernandes, Tanize Stuker (2016)
The phytochemical investigation of methanol crude extract of the stem bark of the species Helietta apiculata Benth and Zanthoxylum fagara (L.) Sarg., Rutaceae, provided the isolation of thirty-one compounds. The species H. apiculata were isolated eight furoquinolínicos alkaloids (8, 9, 10, 11, 12, 13, 15 and 24) and one quinolinone (22), six coumarins (51, 52, 53, 58, 115 and 116), 116 first identified in the literature, three cinnamates (121, 122 and 123), two lignans (98 and 123), a limonoid (92), a long-chain acid (126), a steroid (80) and a mixture terpenes (T39). Two benzophenantridine alkaloids (33 and 34), five amides (69, 70, 117, 118 and 119), and a lignan (124) have been identified in species Z. fagara, along with the steroid 80. The cinnamate 120, 123 and the lignan 119 were first identified as a natural product. The cinnamate 122 and coumarin 115 are first described in H. apiculata species, while the amide 115 is first described in the genus Zanthoxylum, and 119 for the first time in the species Z. fagara. Lignans 98, 123 and 124 are identified in the Rutaceae family first time. The limonoid 92 was subjected to structural modifications through aminolysis reactions with various amines, providing fifteen derivatives, which when subjected to evaluation of the antimicrobial potential demonstrated greater power to inhibition of microorganisms that limonoid. Other derivatives obtained during this study was the acetylation and oxidation products of tembamida (69) amide and methylating the flindersiamina (15) alkaloid. Extracts, fractions and products were subjected to analysis of antimicrobial potential and inhibition of AChE enzyme. The alkaloids showed inhibition potential only for gram-positive bacteria, whereas coumarins were compounds which had the largest range of antimicrobial activities front fungi, Gram-negative and Gram-positive. Inhibition of acetylcholinesterase enzyme was significant only for fractions: ether basic H. apiculata, basic butanol, final aqueous and aqueous extract from the leaves Z. fagara with inhibition values ranging from 58,24% to 74,34% while for isolates the results were not significant.